(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
يهدف هذا البحث إلى إيجاد حلول تامة ذات موجة منعزلة لمعادلة Fitzhugh-Nagumo المعممة ذات الأمثال الثابتة، باستخدام طريقة الدالة الأسية، حيث تم تمثيل أحد هذه الحلول بيانياً. وتبين النتائج التي حصلنا عليها، بمساعدة برامج الحسابات الرياضية مثل Maple وMathematica، أن هذه الطريقة بسيطة ومباشرة وفعالة جداً لحل هذا النوع من المعادلات التفاضلية الجزئية غير الخطية، ولا تتطلب معرفة رياضية متقدمة، ولذلك فهي مناسبة للباحثين العلميين والمهندسين. The goal of this work is finding exact solitary wave solutions to generalized Fitzhug-Nagumo equation with constant coefficients, by using the exp-function method, where we have illustrated graphically one of them, the obtained results, with aid of symbolic programs as Maple and Mathematica, show that this method is simple, direct and very efficient for solving this kind of nonlinear PDEs, and it requires no advanced mathematical knowledge, so it is convenient to scientists and engineering.